2013
DOI: 10.1002/cncr.28201
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial comparing prophylactic upper versus whole‐neck irradiation in the treatment of patients with node‐negative nasopharyngeal carcinoma

Abstract: BACKGROUND:This study sought to compare the clinical outcomes of upper versus whole-neck prophylactic irradiation in the treatment of patients with node-negative nasopharyngeal carcinoma (NPC). METHODS: Between November 2005 and June 2012, 301 patients with node-negative NPC were randomly assigned to receive primary plus prophylactic upper neck irradiation (UNI, 153 patients) or primary plus whole-neck irradiation (WNI, 148 patients). Patients in both groups received irradiation to the primary tumor and the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…We found that patients receiving a BED ≥72 Gy had a similar prognosis to patients receiving a BED <72 Gy in both the small and large ENLN groups, indicating that a total BED of 72 Gy may be sufficient for the ENLNs. Moreover, Li et al [14] also revealed that the administration of 60 Gy in 30 fractions (BED = 72 Gy) to the suspicious node area did not lead to cervical node relapse, further supporting the results obtained in the present study. This finding should be of great importance to clinicians when devising individualized treatment strategies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that patients receiving a BED ≥72 Gy had a similar prognosis to patients receiving a BED <72 Gy in both the small and large ENLN groups, indicating that a total BED of 72 Gy may be sufficient for the ENLNs. Moreover, Li et al [14] also revealed that the administration of 60 Gy in 30 fractions (BED = 72 Gy) to the suspicious node area did not lead to cervical node relapse, further supporting the results obtained in the present study. This finding should be of great importance to clinicians when devising individualized treatment strategies.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have solely focused on the feasibility of omitting irradiation to the lower neck in N0-category NPC [1114]. However, no studies have investigated the optimal radiation dose for the ENLNs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, treatment can include high-risk lymph node regions while sparing low-risk lymph node regions. Although a series of studies reported satisfactory regional control and decreased late normal tissue toxicities for NPC patients after IMRT with selective neck irradiation, geographic misses still occur and may cause unexpected regional failures, such as recurrence in parotid nodes 6-10. Therefore, in this study, we retrospectively analyzed the 5-year treatment results of patients with NPC who were treated with IMRT to identify long-term patterns of regional failure.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the retrospective nature, this study has shown that ENI to the whole neck is not necessary in N0 and N1 (RLN+) group. There was no significant difference in 5 year OS of these subgroups (77.9% vs 79.2%) [27].This study has a long term months (range, 6-84 months), no patient in either group had a cervical node relapse [28]. It would be interesting to know the long term results.…”
Section: Discussionmentioning
confidence: 80%